Entry and competition in mobile app stores - Fiona Scott Morton (Bruegel, 2024)
Entry by rival app stores on the two currently available mobile operating systems is an exciting potential benefit of the European Union's Digital Markets Act (DMA). Apple and Google will need to share the technical specifications of their interfaces with developers and offer them the same functionalities they give to their own stores. The DMA also allows developers to disintermediate the legacy stores entirely by mandating downloads from the web to handsets. These changes should stimulate price competition - resulting in fees falling from the current 30 percent - and competition in variety and features. Privacy and security will be important issues, with the question of who is permitted to offer rival stores being critical. Good enforcement by the European Commission will be necessary to balance gatekeeper rules restricting dangerous services with the need for contestability. The paper concludes with examples of rival app stores that can be expected to enter. Stores will differentiate through curation, such as stores for children, for those trying to reduce their carbon footprints or for those seeking to use public services in a particular country. Some stores will innovate through alternative payment schemes - for example, a newspaper store that enables per-article pricing and pioneers innovative data-sharing policies. Lastly, developers such as Epic have long stated their desire to offer stores with innovative technology.
Keywords: 330